(7-4i)+(9+6i)=

Simple and best practice solution for (7-4i)+(9+6i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7-4i)+(9+6i)= equation:


Simplifying
(7 + -4i) + (9 + 6i) = 0

Remove parenthesis around (7 + -4i)
7 + -4i + (9 + 6i) = 0

Remove parenthesis around (9 + 6i)
7 + -4i + 9 + 6i = 0

Reorder the terms:
7 + 9 + -4i + 6i = 0

Combine like terms: 7 + 9 = 16
16 + -4i + 6i = 0

Combine like terms: -4i + 6i = 2i
16 + 2i = 0

Solving
16 + 2i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + 2i = 0 + -16

Combine like terms: 16 + -16 = 0
0 + 2i = 0 + -16
2i = 0 + -16

Combine like terms: 0 + -16 = -16
2i = -16

Divide each side by '2'.
i = -8

Simplifying
i = -8

See similar equations:

| -6+5a=16+6a | | .25(x-1)+x=1 | | -4y=6y-8 | | 4a-2b-72=0 | | f(x)=-x^2+300x+6 | | 9z-6=9z-6 | | (3x^2)(-5y^3)(-6z)=a | | 5y-(2y+8)=16 | | 40k-24=60k+12 | | [5(x+7)-11]-[3(x-9)+12]= | | 11u^2-13u+2=0 | | 4b+4=4b-1 | | 4f^2+12f+9=0 | | yr-r=5n-6h | | 2x-20=x+15 | | .15y+.07(y+9000)=1290 | | r-6h=5n+yr | | 2+4+(3-4)=3+12 | | 10g+180=3g+54 | | yr+5n=r-6h | | 6(x-1)-x=22-2x | | 40z^2+12-12=0 | | 6x-9=24x+3 | | V-7v=12 | | 15=4(x-3)-(x-9) | | 9=-5n+1+3 | | 4x^2-4x+7x-7=2x-1 | | -4+9(6y+3)=(4y-5)-4 | | 4(x-5)+12=8 | | 32x+4y=0 | | f(x)=50cos(7*(x^6)) | | (x+1)(3x+1)=96x^2 |

Equations solver categories